Risks related to a possible reduction of the waiting period for dogs after rabies antibody titration to 30 days compared with 90 days of the current EU legislative regime. (2nd June 2022) - ,; Alvarez, Julio; Nielsen, Søren Saxmose; Robardet, Emmanuelle; Stegeman, Arjan; Van Gucht, Steven; Vuta, Vlad; Antoniou, Sotiria‐Eleni; Aznar, Inma; Papanikolaou, Alexandra; Roberts, Helen Clare
Abstract: EFSA received a mandate from the European Commission to assess the risks related to a possible reduction of the waiting period after rabies antibody titration test to 30 days compared with 90 days of the current EU legislation, for dogs moving from certain non‐EU countries to the EU. This Scientific Report assessed the probability of introduction of rabies into the EU through commercial and non‐commercial movements of vaccinated dogs with a positive titration test (≥ 0.5 IU/mL) if the waiting period decreases from 90 to 30 days. Assuming that all the legal requirements are complied with, the risk of transmission of rabies through the movement of a vaccinated dog is related to the risk of introducing an animal incubating rabies that was infected before the day of vaccination or shortly after vaccination but before the development of immunity (21 days post‐vaccination). Using published data on the incubation period for experimental and field cases in dogs and considering the rabies incidence data in certain countries, the aggregated probability for the annual introduction of rabies through dogs was assessed. Considering the uncertainty related to the duration of the incubation period, the number of imported dogs, and the disease incidence in some countries it was concluded with a 95% certainty that the maximum number of rabies‐infected imported dogs complying with the regulations in a 20‐year period could increase from 5 to 20 when decreasing the waiting period from 90 to 30 days. Nevertheless, the potential impact of even a small increase in probability means the risk is increased for a region like the EU where rabies has long been a focus for eradication, to protect human and animal health.